HOLISTIC MANAGEMENT OF A 69 YEAR OLD FEMALE PATIENT WITH LOW BACK PAIN AND GRADE 2 HYPERTENSION IN A PRIMARY HEALTH CARE - Adli, Farhan Kamali; Karyus, Aila; Ernawati, Tutik (CV. Jasa Sukses Abadi, 2023)
Based on data from the World Health Organization, it is estimated that around 15-20% of the world's population suffers from hypertension and Hypertension in Indonesia is the third cause of death in all age groups, namely around 6.7% of the total population of deaths in Indonesia. The prevalence of musculoskeletal diseases in Indonesia is 11.9% and based on symptoms, the prevalence of musculoskeletal diseases in Indonesia reaches 24.7%. Meanwhile, the prevalence of musculoskeletal disease in Lampung reached 18.9%. Apply the principles of family medicine services to patients and carry out holistic management based on the patient problem found with patient-centered approach, family focused, and community oriented based on Evidence Based Medicine. This study is a case report with Primary data obtained through history taking, physical examination and home visits to complete family, psychosocial and environmental data. Secondary data was obtained from the patient's medical record. The assessment is based on a holistic diagnosis from the beginning, process, and end of the study. Mrs. L 69 years old, came with complaints of headaches, heavy shoulders and lower back pain. The patient was diagnosed as hypertension and low back pain. In this case, the diagnosis and treatment were carried out according to the theory and related journals. After the intervention, there was a decrease in clinical symptoms and an increase in patient and family knowledge. Holistic management can improve the knowledge, attitudes, and behavior of patients and family in maintaining their health.